(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
Implementing a smart grid integrates modern digital technologies, including monitoring systems, two-way communication capabilities, and automated control mechanisms, to enhance the grid’s overall efficiency. Maintaining voltage within specified ranges is a crucial duty of a distribution network operator. The voltage of the smart grid depends on the generating source, type of electrical load, and distance of the transmission line. This paper introduces a novel method for real-time voltage regulation of a smart grid using Internet of Things (IoT) technology. This paper aims to enhance the voltage stability of the system by overseeing voltage levels at various nodes within a smart grid and choosing and operating the appropriate correction mechanism. The adjustment mechanisms to be done are dynamically varying the excitation current of generators in a thermal power station and dynamically operating the switched capacitor bank and reactor, which are geographically located in different locations, using IoT. Feed-forward control is proposed in the automatic voltage regulator (AVR) at the generator side for efficient voltage control in smart grids with reduced response time for issues. The stress on the distribution network operator can be decreased in maintaining grid voltage.